2014
DOI: 10.1002/anie.201310565
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Electrosynthesis of Rare 1,2,3,16‐Functionalized [60]Fullerene Derivatives

Abstract: Fullerene derivatives with different addition patterns exhibit different physical, chemical, and biological properties, which are important for fullerene applications. Novel and rare 1,2,3,16-functionalized [60]fullerene derivatives having a five-membered heterocycle fused to a [5,6]-junction were obtained with high regioselectivity by electrochemical derivatization of a [60]fulleroindoline. The product structures were determined by spectroscopic data and single-crystal X-ray analysis. The obtained high regios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 34 publications
5
34
0
Order By: Relevance
“…Only one isomeric monocycloadduct is usually formed, up to 8 regioisomeric biscycloadducts have been isolated from cycloaddition reactions of C 60 [8]. On the other hand, the regioisomers of tetrafunctionalized C 60 derivatives reported most commonly are 1,2,3,4-isomers (A) [9][10][11][12][13][14], 1,4,11,15-isomers (B) [15][16][17][18], 1,2,4,15-isomers (C) [19][20][21][22][23], and 1,2,3,16-isomers (D) [24][25][26][27][28][29], while for the hexafunctionalized C 60 derivatives, the most frequently encountered regioisomers are 1,2,3,4,5,6-isomers (E) [30][31][32] and 1,2,4,11,15,30-isomers (F) [15][16][17][18][33][34][35] (Figure 1). Although the elegant templated multifunctionalizations of fullerenes have been devised to realize high regioselectivity [8,36], the regiocontrol on the formation of a specific isomer of biscycloadducts and multicycloadducts is still a daunting task.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one isomeric monocycloadduct is usually formed, up to 8 regioisomeric biscycloadducts have been isolated from cycloaddition reactions of C 60 [8]. On the other hand, the regioisomers of tetrafunctionalized C 60 derivatives reported most commonly are 1,2,3,4-isomers (A) [9][10][11][12][13][14], 1,4,11,15-isomers (B) [15][16][17][18], 1,2,4,15-isomers (C) [19][20][21][22][23], and 1,2,3,16-isomers (D) [24][25][26][27][28][29], while for the hexafunctionalized C 60 derivatives, the most frequently encountered regioisomers are 1,2,3,4,5,6-isomers (E) [30][31][32] and 1,2,4,11,15,30-isomers (F) [15][16][17][18][33][34][35] (Figure 1). Although the elegant templated multifunctionalizations of fullerenes have been devised to realize high regioselectivity [8,36], the regiocontrol on the formation of a specific isomer of biscycloadducts and multicycloadducts is still a daunting task.…”
Section: Introductionmentioning
confidence: 99%
“…The electrophilic-to-nucleophilic reactivity reversal of fullerenes and their derivatives caused by electrochemical reduction opens a new territory in fullerene chemistry and has demonstrated increasing importance in the efficient synthesis of novel fullerene derivatives [37], including the abovementioned types A, C, and D [11,19,[25][26][27][28][29]. It was interestingly found that the same dianionic [60]fulleroindoline (1a 2-, vide infra) behaved differently toward alkylating and acylating reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PEG-C60(OH)16-24-DOX completely inhibited angiogenesis at the concentration of 100 µM (calculated by DOX) and DOX alone did not show any inhibition. In other model to detect endothelial tubulogenesis, PEG-C60(OH)16-24-DOX strengthened the tubulogenesis inhibition of either C60(OH) [16][17][18][19][20][21][22][23][24] or DOX at the concentration of 1 µM and it did not bear the cytotoxicity [38].…”
Section: Radical Scavenger: Prevent Oxidative Damage From Dox and Ccl4mentioning
confidence: 99%
“…One of the main objective of fullerene chemistry is the production of well‐defined, stable and characterizable adducts , , . However, various reactions on C 60 usually lead to a complex mixture containing mono‐adducts together with several bis‐ or multi‐adduct isomers, which possess different molecular structures but similar chromatographic properties, making the subsequent separations rather tricky . In fullerene chemistry, accordingly, it is desirable to develop highly regioselective synthetic methods to get merely mono‐adducts for sake of further structural characterizations and applications as well.…”
Section: Introductionmentioning
confidence: 99%